2010
DOI: 10.1111/j.1365-3148.2010.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of intravenous immune globulin in the ICU: a retrospective review of prescribing practices and patient outcomes

Abstract: IVIG is used relatively infrequently in the critical care setting. The most common indications were GBS, TEN and NF. Mortality was high. There was no difference between community and academic ICUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 16 publications
3
31
1
Order By: Relevance
“…Our study observed a relatively high overall same‐day TE incidence rate of 1%, with rates ranging up to 2% for specific products, which was consistent with existing literature showing TE rates from 0.6% to 5% after IG exposure 2,4,11,12,39‐43 . The study results showed that venous same‐day TEs were more common than arterial TEs.…”
Section: Discussionsupporting
confidence: 91%
“…Our study observed a relatively high overall same‐day TE incidence rate of 1%, with rates ranging up to 2% for specific products, which was consistent with existing literature showing TE rates from 0.6% to 5% after IG exposure 2,4,11,12,39‐43 . The study results showed that venous same‐day TEs were more common than arterial TEs.…”
Section: Discussionsupporting
confidence: 91%
“…A study of IVIG use in an adult ICU revealed 19% of IVIG prescriptions were for 'appropriate' indications and 7% were 'inappropriate'. The remaining 74% were prescribed for indications with some evidence to support their use 10 . In this study GBS was a common indication despite the presence of other therapeutic alternatives .A study reported that , in children with GBS requiring mechanical ventilation, Plasmapaharesis was superior to IVIG regarding the duration of Mechanical ventilation but not PICU stay or the short term neurological outcome 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous Ig is well tolerated in people, with less than 5% of patients suffering from adverse effects after transfusion . The most common side effect of hIVIG use is acute hypersensitivity; other reported complications include thromboembolism, renal failure, hypotension, aseptic meningitis, and fluid overload . Veterinary patients exposed to hIVIG are at risk for these same complications, but carry a higher risk of reaction as hIVIG administration involves xenoprotein introduction to the body.…”
Section: Adverse Effects Of Ivig Administrationmentioning
confidence: 99%
“…Thromboembolic events including deep vein thrombosis, myocardial infarction, pulmonary embolism, central retinal vein occlusion, cerebro‐vascular accidents, and hepatic veno‐occlusive disease have been reported in people following hIVIG transfusion . A 2009 study by Tsuchiya et al revealed increased concentrations of circulating thrombin‐antithrombin complexes and fibrinogen degradation products in healthy beagles receiving human Ig, and concluded that hIVIG administration promotes hypercoagulability in dogs .…”
Section: Hypercoagulationmentioning
confidence: 99%